Karrieren ostdeutscher Physikerinnen in Wissenschaft und Forschung 1970 bis 2000 - Amos, Heike 1962- (Quellen und Darstellungen zur Zeitgeschichte, 2020)
How did German reunification impact career opportunities for female East German physicists? Heike Amos investigates the broader consequences of reunification by looking specifically at the example of female physicists. Drawing on many unpublished documents and interviews conducted by the author, she describes the "feminine" and "masculine" development of science in the new German states